2019
DOI: 10.1111/jcmm.14303
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin in transdifferentiated hepatocyte proliferation and function in serum‐free medium

Abstract: Transdifferentiated hepatocytes are potential seeding cells for bioartificial liver (BAL) treatment, and it is important to obtain a sufficient number of functional hepatocytes in serum‐free medium (SFM). Although insulin plays an essential role in promoting cell proliferation and metabolism, the functions of insulin in transdifferentiated cells remain poorly understood. Here, we found that 1.0 mg/L insulin significantly increased human‐induced hepatocyte‐like cells (hiHeps) proliferation and viability in SFM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…cDNA was obtained using MLV reverse transcriptase (Promega, USA). Quantitative real-time PCR (qRT-PCR) was performed as previously reported [23]. GAPDH was used as an endogenous control.…”
Section: Rna Isolation and Qrt-pcrmentioning
confidence: 99%
“…cDNA was obtained using MLV reverse transcriptase (Promega, USA). Quantitative real-time PCR (qRT-PCR) was performed as previously reported [23]. GAPDH was used as an endogenous control.…”
Section: Rna Isolation and Qrt-pcrmentioning
confidence: 99%
“…In previous studies, glucose consumption in normal cells was used as the control [24,25], but we found that insulin has a mitogenic effect on hepatocytes, although there were no changes in proliferation rate within a certain concentration range. This has also been described by other investigators [31,32]. Since cell proliferation affects glucose consumption, we compared cells with similar proliferation rates but selected those with the highest glucose consumption within each group as the control; IR was identified based on a decrease in glucose consumption.…”
Section: Discussionmentioning
confidence: 90%
“…Quantitative real-time polymerase chain reaction (qRT-PCR) and western blot in this study were performed as previously published articles. [14,15] The primer sequences are shown in Table S1; GAPDH was used as the housekeeping gene. The primary antibodies are shown in Table S2, and β-actin served as the internal control.…”
Section: Qrt-pcr and Western Blottingmentioning
confidence: 99%
“…[13,14] Further, a large-scale expansion technique of hiHeps based on serumfree microcarriers has been established to achieve high-density cell culture. [15] However, the expression of the hepatocyte-specific functions of hiHeps is still premature compared to that of primary hepatocytes in vitro, especially for urea synthesis and CYP450 enzyme activity. The expression of some metabolism-related genes and coagulation-related genes has been shown to be significantly improved when hiHeps are incorporated into the liver, suggesting that the liver function of hiHeps can be enhanced by simulating an in vivo microenvironment.…”
Section: Introductionmentioning
confidence: 99%